Metagenomic Analysis Identifying a Rare Leishmania Infection in an Adult With AIDS - Song, Pingping; Chen, Shuai; Tan, Xiaoyu; Gao, Yanjun; Fu, Juanjuan; You, Zhiqing; Wang, Chengtan; Zhao, Qigang; Pang, Feng (Frontiers in Cellular and Infection Microbiology, 2021)
Leishmania belongs to a genus of the protozoan parasites that causes leishmaniasis, and includes cutaneous leishmaniasis (CL) and visceral leishmaniasis (VL). In this case, Leishmania amastigotes were found on cytomorphology examination of the bone marrow specimen, followed by 1,076 Leishmania donovani reads using metagenomic next generation sequencing (mNGS). Since being definitely diagnosed with VL/HIV coinfection, the patient was treated with liposomal amphotericin B as the parasite-resistant therapy and was discharged after clinical cure. But nearly a year later, on the mNGS follow-up, L. donovani was detected in the patient’s blood plasma specimen with 941 reads, suggesting that a relapse of leishmaniasis had occurred. These results indicate that leishmaniasis still exists in China and may represent a public health concern. This case could be helpful in the differential diagnosis of leishmaniasis, and for determining disease progression, prevention, and control of vectors and reservoir hosts.